Modulating gut microbiota and metabolites with dietary fiber oat β-glucan interventions to improve growth performance and intestinal function in weaned rabbits - Ma, Li; Luo, Zhengzhong; Huang, Yixin; Li, Yan; Guan, Jing; Zhou, Tao; Du, Zhenlong; Yong, Kang; Yao, Xueping; Shen, Liuhong; Yu, Shumin; Zhong, Zhijun; et al. (Frontiers in Microbiology, 2022)
The effect of oat β-glucan on intestinal function and growth performance of weaned rabbits were explored by multi-omics integrative analyses in the present study. New Zealand White rabbits fed oat β-glucan (200 mg/kg body weight) for 4 weeks, and serum markers, colon histological alterations, colonic microbiome, colonic metabolome, and serum metabolome were measured. The results revealed that oat β-glucan increased body weight, average daily gain, average daily food intake, and decreased serum tumor necrosis factor-α, interleukin-1β, and lipopolysaccharide contents, but did not affect colonic microstructure. Microbiota community analysis showed oat β-glucan modulated gut microbial composition and structure, increased the abundances of beneficial bacteria Lactobacillus, Prevotellaceae_UCG-001, Pediococcus, Bacillus, etc. Oat β-glucan also increased intestinal propionic acid, valeric acid, and butyric acid concentrations, decreased lysine and aromatic amino acid derivative contents. Serum metabolite analysis revealed that oat β-glucan altered host carbohydrate, lipid, and amino acid metabolism. These results suggested that oat β-glucan could inhibit systemic inflammation and protect intestinal function by regulating gut microbiota and related metabolites, which further helps to improve growth performance in weaned rabbits.